Organizational culture from the point of view of employees of socionomic professions with different levels of job satisfaction - Fofanova, Galina A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The results of the empirical research aimed at identifying organizational culture from the point of view of employees of socionomic professions with different levels of job satisfaction are presented in the article. Once the real and preferred type of organizational culture coincidence, the employee is claimed to have a high level of job satisfaction. Representatives of socioeconomic professions, in general, consider the indicated actual type of culture bureaucratic and at the same time strive for a clan type of organizational culture. There is a large gap between the current and preferred type of organizational culture. However, the further respondents are from actually helping professions (meaning non-socioeconomic specialties, borderline professions), the more satisfied they are with their work. Although the clan organizational culture for the entire sample as a whole is designated as the most preferred. The possibilities of practical application of the results and prospects for more advanced studies are considered.
Keywords: job satisfaction; socionomic professions; organizational culture